Risk Premium and Volatility Analysis on Indonesia Stock Exchange - Syanindita Prameswari; Adler Haymans Manurung (Jurnal Indonesia Sosial Teknologi, 2024)
Market risk premium and market volatility are important in investment decisions. Volatility is an important variable in derivative securities which is a measure of changes in stock returns. The research focuses on stock return volatility, research that points to a risk premium in emerging markets. The purpose of this study is to explain the relationship between market equity premium and volatility using GARCH (1.1) on the Indonesia Stock Exchange. This research uses daily closing price data of the Indonesia Stock Exchange Composite Index (JCI). The result of this study, that there is a relationship between risk premium and volatility in the Indonesian stock market. The conclusion of this study is to try to test whether there is a relationship from the volatility of return to risk premium in the Indonesian stock market. Using the daily trend of the Indonesian stock market (IDX) from January 2010 to September 2023.